‘The Work of National Revival Must Begin... with the Working People’: A New Role Model for Female Workers in the Kraków-based Kobieta Polska (1916–1921) - Dormus, Katarzyna (Paedagogia Christiana, 2026)
The period of the First World War, along with the emerging prospect of Poland regaining independence, intensified public discourse on the need to prepare society for the imminent political and social transformation. Particular attention was directed toward the working-class population, which also became a subject of interest for the Catholic Church. It soon became apparent that the specific needs and challenges of female workers required a distinct and targeted approach. In 1915, the Union of Catholic Associations of Working Women and Girls was established in the Kraków diocese. The following year, it launched Kobieta Polska (The Polish Woman), a monthly magazine edited by Father Ludwik Kasprzyk, serving as the official publication of the organization. The magazine’s primary objective was to prepare female workers for life in an independent Polish state through religious education, the promotion of traditional roles as mothers and homemakers, and the instillation of a sense of solidarity within their social class.